PRODUKTIVITAS DAN STRATEGI PENGEMBANGAN KAPAL POLE AND LINE TERHADAP SUMBERDAYA IKAN CAKALANG (KATSUWONUS PELAMIS) DI KOTA KUPANG NTT - Edizul A. Sadir; Mukhlis Ali; Agustinus A.H. Ratung; Charlens Polin; I Made Aryana; Sakti Pandopotan Nababan; Ahmad Hanifah (Fakultas Teknologi Lingkungan dan Mineral - Universitas Teknologi Sumbawa, 2025)
The skipjack tuna fishery in NTT plays a vital role in the regional economy, therefore, a study of fishing productivity is necessary to understand the relationship between fishing effort, yield, and stock condition. This study aims to analyze skipjack tuna fishing productivity, assess the energy efficiency of local fishermen, and formulate a sustainable management strategy. The methods used were surveys and field observations, with analysis using CPUE, energy efficiency, and productivity per vessel/fisherman. Management strategies were developed using a SWOT matrix and QSPM. The results showed the highest CPUE in October–November (272.3 kg/trip), vessel productivity 6.9 kg/trip, and fisher productivity 25 kg/person/trip. The highest fuel efficiency was recorded in January (2.1 L/kg of fish). Management strategies include improving catch quality, developing business capital assistance, and renewing the Pole and line skipjack tuna fleet.